Xpointer : an x-ray telepointer for relaxed-space-time wysiwis and unconstrained collaborative 3d design systems - Agustina (2013)
Telepointers are a real-time collaborative feature to indicate pointing at shared objects. Existing telepointing techniques are, however, restricted to pointing at the foremost object underneath a mouse cursor in relaxed-space but strict-time WYSIWIS environments. In real-time collaborative 3D design systems with animation creation capabilities, multiple 3D objects can be simultaneously visible underneath mouse cursors for users to freely and concurrently work on and point at (unconstrained collaboration), and multiple users can view 3D workspaces and point from different viewing perspectives (relaxed-space WYSIWIS) and animation time frames (relaxed-time WYSIWIS). This paper contributes a novel XPointer technique with the capability of pointing through objects correctly and consistently from different viewing perspectives and time frames, even in the presence of concurrent editing work. This work is the first to identify and address these advanced 3D telepointing needs and capabilities, and to extend the concept of relaxed WYSIWIS to include the time aspect. The XPointer has been implemented in the CoMaya real-time collaborative 3D design system (demonstration video: http://cooffice.ntu.edu.sg/comaya/videoXPointer.php).